The Differential Effects of Progressive Relaxation and Imagery on Anxiety - Schubert Walker, Lilly; Busby, Keith; Walker, James L. (Canadian Journal of Counselling and Psychotherapy, 2011)
The aim of this research was to compare the effects of progressive relaxation and imagery on stress levels. High and low anxiety subjects were selected on the basis of scores on the State- Trait Anxiety Inventory, and were randomly assigned to Progressive Relaxation or Cognitive Imagery treatment conditions. Results indicated that there were no significant differences between treatment conditions: both treatment groups significantly reduced cognitive anxiety scores Ip < .007) from pre- to posttreatment. The analysis of anxiety scores indicated that high anxious subjects significantly decreased their trait anxiety scores (p < .0003) and somatic anxiety scores ip < .02) while low anxious subjects increased their trait anxiety scores (p <C .006). The results of this study are discussed in order to help professionals in consultation to become aware of the importance of anxiety induction as a factor in the course of a relaxation treatment.